Analysis of Factors Influencing Public Trust in the Adoption of Digital Zakat Payment - Suselo, Dedi; Zaenal Abidin, Ahmad; Prasetian Dewi, Arlinta; Eko Sujianto, Agus; Akhyak, Akhyak (El-kahfi | Jurnal Ekonomi Islam, 2025)
Abstract: Public trust in amil zakat institutions is a key factor in optimizing national zakat collection. Although Indonesia has a vast zakat potential, actual collection remains low. One of the main causes is the lack of public trust in zakat management institutions, particularly concerning transparency, accountability, and fund management security. In the context of technological advancement, the digitalization of zakat payment systems emerges as a promising solution to enhance efficiency, accessibility, and public trust. This study aims to analyze the factors influencing public trust in digital zakat platforms, using the National Amil Zakat Institution Baitul Maal Hidayatullah (BMH) as a case study. The research adopts a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 150 respondents who are active users of BMH’s digital platform. The analytical method used is exploratory factor analysis to identify the latent structure of variables forming the trust construct. The results indicate three main factors that significantly influence public trust in digital zakat platforms: digital security, transparency and reporting, and ease of use. These three factors show a strong relationship in shaping public perceptions of the credibility of technology-based zakat systems. The findings affirm that trust in digital zakat services is influenced not only by technological factors but also by institutional integrity and the overall quality of user experience.